183k views
1 vote
Given the functions f and g below, find g(f(

daleco
f(x) = (3x +1
g(x) = x2 + 4x + 6

1 Answer

1 vote

Hello.

To do this, we need to work from right to left. (Another way to phrase it is from inside to out).

Step by step:

1). f(x)= 3x+1

2). Take 3x+1 and plug it into wherever you see the variable x in the g(x).

** g(f(x))= (3x+1)² + 4(3x+1) +6

g(f(x))= (3x+1)² + 12x + 4 + 6

g(f(x))= (3x+1)² + 12x + 10

g(f(x))= (3x+1)(3x+1) + 12x + 10

g(f(x))= 9x² + 6x +1 + 12x +10

g(f(x))= 9x² + 18x + 11

Hope that helped.

** this is not proper notation, but rather, a demonstration of how plugging functions into functions would work.

************************

Disclaimer:

Always double check your answer with a reliable source, as mistakes can be made.

User Acdx
by
5.8k points